Manajemen Isu dan Tantangan Masa Depan: Pendekatan Public Relations - ., Prayudi (Jurnal Ilmu Komunikasi, 2007)
Abstract : Issues Management is the management process whose goal is to help preserve markets, reduce risk, create opportunities and manage image as an organizational asset for the benefit of both an organization and its primary stakeholders. This is accomplished by: anticipating, researching and prioritizing issues; assessing the impact of issues on the organization: recommending policies and strategies to minimize risk and seize opportunities, participating and implementing strategy; evaluating program impact. Issues management both as a science and managerial practice has developed dynamically in the past three decades. This paper examines approaches to issues management as a science, corporate social responsibility as a pre-emptive policy of issues management, and issues management as skill for public relations practitioners.